The Influence of the Soviet Legal Model on the Law Directing the Establishment and Operation of Vietnam and China's Central Banks - Nghia, Pham Thi Hong (VNU Journal of Science: Legal Studies; Vol 40 No 1, 2024)
The Soviet legal model significantly influenced the legal stance, operation and organization of central bank branches in China and Vietnam. According to research on the effect of the Soviet legal model on the organization and operations of the Central Bank of China and the Central Bank of Vietnam, the Soviet legal model assisted Vietnam and China in creating major legislative frameworks for the banking sector. However, the legal status of Russian banks has evolved in the direction of being more autonomous and efficient; at the same time, the People's Bank of China branch was also restructured to be more streamlined and efficient. These are the areas in which the State Bank of Vietnam has to improve in order to grow more successfully.